UJI AKTIVITAS EKSTRAK ETANOL BIJI PINANG (Areca catechu L.) TERHADAP PENYEMBUHAN LUKA SAYAT KELINCI (Oryctolagus cuniculus) - Arief Azis (Jurnal Kesehatan Yamasi Makassar, 2022)
Wounds are a condition that is often experienced by everyone, whether with mild, moderate or severe severity. Wounds are the loss or destruction of part of the body's tissues. This study aims to determine how the effect of ethanol extract of areca nut (Areca catechu L.) on the wound healing process in rabbits (Oryctolagus cuniculus). The method used in the manufacture of extracts is by maceration using 70% ethanol as a solvent. The test animals were divided into 5 groups consisting of 3 test animals. Group I was given Na-CMC as a negative control, group II was given 3% betel nut ethanol extract, group III was given 5% betel nut ethanol extract, group IV was given 7% ethanol extract, and group 5 was given Nebacetin powder as a positive control. . The results of this study showed that pinan seed ethanol extract could acc elerate wound healing in rabbits at a maximum concentration of 7%. The results of the Anova statistical test on cuts in rabbits using Areca Nut extract obtained a significance value of P > 0.05 (at the 0.05 level, i.e. 0.000 < 0.005). This means that each treatment gives a significant (significant) difference, for this it is necessary to proceed with testing the average difference of each treatment with the LSD Post Hoc tests.